Advanced Percutaneous Mechanical Circulatory Support Devices for Cardiogenic Shock. Issue 11 (November 2017) - Miller, P. Elliott; Solomon, Michael A.; McAreavey, Dorothea
Abstract : Objectives: To review temporary percutaneous mechanical circulatory support devices for the treatment of cardiogenic shock, including current evidence, contraindications, complications, and future directions. Data Sources: A MEDLINE search was conducted with MeSH terms: cardiogenic shock, percutaneous mechanical circulatory support, extracorporeal membrane oxygenation, Impella, and TandemHeart. Study Selection: Selected publications included randomized controlled trial data and observational studies describing experience with percutaneous mechanical circulatory support in cardiogenic shock. Data Extraction: Studies were chosen based on strength of association with and relevance to cardiogenic shock. Data Synthesis: Until recently, there were few options if cardiogenic shock was refractory to vasopressors or intra-aortic balloon pump counterpulsation. Now, several percutaneous mechanical circulatory support devices, including Impella (Abiomed, Danvers, MA), TandemHeart (CardiacAssist, Pittsburgh, PA), and extracorporeal membrane oxygenation, are more accessible. Compared with intra-aortic balloon pump, Impella provides greater hemodynamic support but no reduction in mortality. Similarly, TandemHeart improves hemodynamic variables but not survival. Comparative studies have been underpowered for mortality because of small sample size. Veno-arterial extracorporeal membrane oxygenation offers the advantage of biventricular circulatory support and oxygenation, but there are significant vascular complications. Comparative studies with extracorporeal membrane oxygenation have not been completed. Despite lack of randomized controlled data, there has been a substantial increase in use of percutaneous mechanical circulatory support. Several ongoing prospective studies with larger sample sizes may provide answers, and newer devices may become smaller, easier to insert, and more effective. Conclusions: Mortality from cardiogenic shock remains unacceptably high despite early coronary revascularization or other therapies. Although evidence is lacking and complications rates are high, improvements and experience with percutaneous mechanical circulatory support may offer the prospect of better outcomes.